Pengaruh Model Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa - Rini Nurbayti; Hilmi Hambali; Muhammad Wajdi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to determine the effect of the Problem Based Learning model on the critical thinking skills and cognitive learning outcomes. This type of research is True Experimental with pretest-posttest Control Group Design. The results of the research show that the average critical thinking ability and cognitive learning outcomes of students in the experimental class taught using the Problem Based Learning model are in the sufficient category with an average score of critical thinking ability of 61.69 and an average score of cognitive learning outcomes. 66.73 with students who achieved the KKM of 35%, while in the control class with the Discovery Learning model it was also in the sufficient category with an average critical thinking ability score of 49.00 and cognitive learning outcomes with an average of 44.23 with students who achieved the KKM. by 4%. Inferential analysis shows significant results with a value of sig>0.05 so that there is an influence of the Problem Based Learning learning model on critical thinking skills and student learning outcomes.